Factors Associated with Surgical Timeliness during the COVID-19 Pandemic in Medellin, Colombia: a Cross-sectional Study - Gutiérrez Gutiérrez, Cristian Camilo; Quiñones Córdoba, Natalia; Gómez Restrepo, Nohemí Yeraldin; G; Arteaga Noriega, Anibal Vicente (Enfermería Cuidándote, 2026)
Introduction: The COVID-19 pandemic drastically disrupted healthcare systems worldwide, causing significant delays in surgical care and jeopardizing the timeliness and safety of procedures. The objective was to describe the factors associated with surgical opportunity in patients operated in a high complexity institution in Medellin, Colombia, during the COVID-19 pandemic. Methodology: A descriptive study with a cross-sectional analytical component was carried out, including the medical records of 128 patients by census of the period, who were operated on in the period from 2020 July to December. Patients operated under any anesthetic technique (general or regional) of legal age and who were treated in the IPS of the study were included. Procedures performed under local anesthesia or sedation were excluded. For quantitative variables, the Mann-Whitney U test and kruskal wallis test were used to compare with the dependent variable. For each of the analyses, a significance for hypothesis testing (α) of 5% was used, with 95% confidence. Results and Discussion: It was found that surgical timeliness times were higher in patients coming from outpatient services (p=0.001). It was also observed that professional nurses performed antisepsis in surgeries with better surgical timeliness and that auxiliary nurses performed antisepsis in surgeries with more days (p=0.001). Patients who did not require ICU postoperatively had higher median surgical timeliness (p=0.891), and elective surgery patients had longer waiting times (p=0.001). The involvement of nursing staff in antisepsis was associated with shorter times, underscoring its importance in process optimization. Conclusion: The results show that surgical timeliness is influenced by multiple factors, including the patient’s origin, surgical specialty, type of procedure and personnel involved in asepsis. Patients from outpatient services and those undergoing procedures such as prosthesis replacement and saphenectomy presented longer waiting times. Further studies are required for a better understanding of the phenomenon.